Assisted reproductive technologies are associated with limited epigenetic variation at birth that largely resolves by adulthood - Boris Novakovic; Sharon Lewis; Jane Halliday; Joanne Kennedy; David P. Burgner; Anna Czajko; Bowon Kim; Alexandra Sexton-Oates; Markus Juonala; Karin Hammarberg; David J. Amor; Lex W. Doyle; et al. (NATURE PUBLISHING GROUP, 2022)
More than 7 million individuals have been conceived by Assisted Reproductive Technologies (ART) and there is clear evidence that ART is associated with a range of adverse early life outcomes, including rare imprinting disorders. The periconception period and early embryogenesis are associated with widespread epigenetic remodeling, which can be influenced by ART, with effects on the developmental trajectory in utero, and potentially on health throughout life. Here we profile genome-wide DNA methylation in blood collected in the newborn period and in adulthood (age 22-35 years) from a unique longitudinal cohort of ART-conceived individuals, previously shown to have no differences in health outcomes in early adulthood compared with non-ART-conceived individuals. We show evidence for specific ART-associated variation in methylation around birth, most of which occurred independently of embryo culturing. Importantly, ART-associated epigenetic variation at birth largely resolves by adulthood with no direct evidence that it impacts on development and health.